THE ROLE OF MACROPHAGES IN THE RETENTION AND TRANSFORMATION OF PIGMENT IN THE SKIN – THE IMMUNOLOGY OF TATTOOS - Kosowska, Amelia; Kosowska, Michalina; Radzka, Marlena; Radzka, Izabela; Jankowska, Justyna; Rataj, Jonatan; Harenza, Kamil; Ollik, Karolina Sara; Kukulska, Magdalena Barbara; Kowalczyk, Michał (International Journal of Innovative Technologies in Social Science, 2025)
Tattooing involves intradermal deposition of pigment that elicits a long‑lasting immune response. Dermal macrophages play a key role in maintaining pigment by capturing pigment particles and retaining them inside their phagolysosomes. The aim of this paper is to analyze the mechanisms of phagocytosis of tattoo pigment by dermal macrophages, their impact on tattoo persistence, and to assess the significance of phenotypic differentiation (M1/M2) in the context of inflammation, laser therapy, and potential biomedical applications. We reviewed data from recent experimental studies, including 3D skin models, electron microscopy, flow cytometry, and TPE‑FLIM imaging. We also considered the effect of pigment chemical composition on activation of immune cells. Dermal macrophages demonstrate high efficiency in phagocytosis and long‑term storage of pigment. The observed “capture–release–recapture” mechanism ensures pigment stability despite natural cellular turnover. Pigment composition influences macrophage polarization (M1 or M2), which may determine chronic inflammation versus regeneration. Understanding macrophage–pigment dynamics provides new insights into tattoo durability and opens opportunities to improve the effectiveness of laser removal. Advances in imaging and the use of biosensor cells point to potential future applications of tattoos in diagnostic and regenerative medicine.